ECML PKDD 2018 Workshops: DMLE 2018 and IoTStream 2018, Dublin, Ireland, September 10-14, 2018, Revised Selected Papers - Monreale, Anna; Alzate, Carlos; Kamp, Michael; Krishnamurthy, Yamuna; Paurat, Daniel; Sayed-Mouchaweh, Moamar; Bifet, Albert; Gama, João; Ribeiro, Rita P (Communications in Computer and Information Science, 2019)
This book constitutes revised selected papers from the workshops DMLE and IoTStream, held at the 18thEuropean Conference on Machine Learning and Knowledge Discovery in Databases, ECML PKDD 2018, in Dublin, Ireland, in September 2018. The 8 full papers presented in this volume were carefully reviewed and selected from a total of 12 submissions.The workshops included are:DMLE 2018: First Workshop on Decentralized Machine Learning at the EdgeIoTStream 2018: 3rd Workshop on IoT Large Scale Machine Learning from Data Streams